Evolution of the nexus as a policy and development discourse - Pandey, Vishnu Prasad; Shrestha, S. (2017)
The key resources that sustain life and the ecosystem (e.g., water, food, energy, and others) are linked in many ways. Action in one sector might have impacts on others, thus forming a policy nexus among them. The relationships between the resources were realized long back; however, the nexus concept is still evolving as a policy and development discourse with the involvement of many actors. It is generally considered as a “multicentric” approach, the advancement of “water centric” Integrated Water Resources Management (IWRM). This chapter presents a systematic review on how the nexus concept emerged and is now spreading to cover wider sectors; it then discusses key actors involved in raising the profile of the nexus as a policy and development discourse.